Adverse Childhood Experiences and Psychological Well-Being in Chinese College Students: Moderated Mediation by Gender and Resilience - Chen, Yafan; Hua, Kai; Huang, Chienchung; Zhou, Gaosheng; Wang, Jianfeng (Frontiers in Psychiatry, 2021)
Adverse childhood experiences (ACEs), including child abuse/neglect and household challenges, are a prevalent social issue that impacts individuals’ well-being worldwide. Relatively few ACEs studies orient to the presence of psychological wellness, especially in ethnically Chinese populations. Furthermore, less is known about resilience as a mechanism between ACEs and psychological well-being, in addition to the moderating effect of gender. This study examined the relationship between ACEs and psychological well-being among Chinese college students and the potential mediating and moderating effects of resilience and gender, respectively. A total of 1,871 college students studying social science from 12 Chinese colleges completed an anonymous online survey between late September and early October 2020. Multiple-group path analyses were conducted to examine whether the relationships among ACEs, resilience, and psychological well-being differed as a function of gender. Results suggested that gender moderated the relationships studied. For female students, resilience mediated the association between abuse/neglect and psychological well-being, where abuse/neglect was negatively associated with resilience, which in turn had a negative relationship with psychological well-being. For male students, household challenges were negatively related to psychological well-being through reduced resilience. Based on the findings, various ACE-informed initiatives may be essential to prevent and protect individuals from ACEs. We also call for resilience-based interventions to enhance individuals’ resilience and thus strengthen their psychological well-being.